Fear of Relationship Loss: Attachment Style as a Vulnerability Factor in Job Burnout - Pšeničny Andreja; Perat Mitja (Sciendo, 2020)
To investigate the correlation between attachment styles and various burnout risk groups ("relaxed", "wornout", "challenged" and "burnout") and whether attachment styles suitably discriminate between individual burnout risk groups.